592 A Large Lipoma: An Unusual Presentation of the Tongue. (12th October 2021) - Shathur, A; Rashid, A; Patel, V; Ffolkes, L; Jayaram, R
Abstract: Background: Lipomas are commonly identified tumours of the body however they are rarely found in the oral cavity. Rarer still is it to report a case of a lipoma in the tongue as they are more commonly located in the buccal mucosa. Objectives: To diagnose and explore the pathogenesis of a soft-tissue swelling of unknown origin Method: A thorough patient history and clinical examination was undertaken followed by magnetic resonance imaging (MRI) which revealed an alarming report at first glance. An incisional biopsy of the lesion was then carried out to aid in diagnosing the lesion. Results: The swelling caused the patient no pain however the mere size of the lesion affected the patient's tongue movement and function which therefore affected the patient's quality of life. The imaging and the biopsy of the lesion led to a diagnosis of a large lipoma on the lateral border of the tongue. Conclusions: To the authors' best knowledge, we present a rare case of a patient whom we diagnosed with a large lipoma on the lateral border of the tongue. This case report discusses the stages of patient management from initial presenting complaint, up to the maintenance of the patient following the diagnosis of this lesion.